Lightroom Classic CC and Photoshop Workflows: Start-to-Finish Studies. - Kost, Julieanne (linkedin.com, 2017)
Learn Lightroom Classic CC and Photoshop workflow and image editing techniques by watching five images edited from start to finish beginning in Lightroom and ending in Photoshop.